A Comparative Biochemical Study Between Patient’s Obese and Healthy - Salman, Asmaa; Saifullah, Perry (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Objectives: Obesity rates have increased globally with increase in the incidence of comorbidities especially type 2 diabetes mellitus. A cross-sectional study was conducted on healthy obese adults to estimate: (i) comparisons of anthropometric indicators, lipid profile, and glycemic profile in obese compared with non-obese, and (ii) the association of anthropometrics and lipid profile with glycemic profile in obese adults. Methods: The study includes 120 individual with aged ranged (25 – 55) years were enrolled in this study. They were divided into two groups: group one (G1) consist of 90 patients with a body mass index (BMI) of more than 25 kg/m2. Group two (G2) of 30 healthy adults as a control group with (BMI) of less than 25 kg/m2.waist circumference (WC), hip circumference (HC), and waist/hip ratio (WHR) as anthropometric indicators, and fasting serum lipid profile, glycated hemoglobin (HbA1c), and Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) as biochemical variables were assessed. Statistical significance (α) was set at (p<0.05).Results: Based on independent samples T-test analysis acted as a significant comparison between non-obese and obese groups, anthropometrics and biochemical variables exhibited highly significant higher in obese compared with non-obese. Also, a positive significant correlation was found between WC and WHR with both of HOMA-IR and HbA1c. Finally, a positive significant association of HOMA-IR with triglycerides (TG), total cholesterol (TC), very low-density lipoprotein cholesterol (VLDL-C), low-density lipoprotein cholesterol (LDL-C) except for high-density lipoprotein cholesterol (HDL-C), no significance was found as well as HbA1c showed only positive significant association with LDL-C. In conclusion, the present study demonstrated that WC was the strongest indicator for increasing HOMA-IR than WHR. Also, this study revealed that abnormalities in lipid profile in obese participants have shown strong positive association with HOMA-IR, particularly LDL-C.